Manganese Doped Fluorescent Paramagnetic Nanocrystals for Dual‐Modal Imaging. Issue 23 (8th August 2014) - Sharma, Vijay Kumar; Gokyar, Sayim; Kelestemur, Yusuf; Erdem, Talha; Unal, Emre; Demir, Hilmi Volkan
<x xml:space="preserve">Abstract</x> In this work, dual‐modal (fluorescence and magnetic resonance) imaging capabilities of water‐soluble, low‐toxicity, monodisperse Mn‐doped ZnSe nanocrystals (NCs) with a size (6.5 nm) below the optimum kidney cutoff limit (10 nm) are reported. Synthesizing Mn‐doped ZnSe NCs with varying Mn2+ concentrations, a systematic investigation of the optical properties of these NCs by using photoluminescence (PL) and time resolved fluorescence are demonstrated. The elemental properties of these NCs using X‐ray photoelectron spectroscopy and inductive coupled plasma‐mass spectroscopy confirming Mn2+ doping is confined to the core of these NCs are also presented. It is observed that with increasing Mn2+ concentration the PL intensity first increases, reaching a maximum at Mn2+ concentration of 3.2 at% (achieving a PL quantum yield (QY) of 37%), after which it starts to decrease. Here, this high‐efficiency sample is demonstrated for applications in dual‐modal imaging. These NCs are further made water‐soluble by ligand exchange using 3‐mercaptopropionic acid, preserving their PL QY as high as 18%. At the same time, these NCs exhibit high relaxivity (≈2.95 mM−1 s−1) to obtain MR contrast at 25 °C, 3 T. Therefore, the Mn2+ doping in these water‐soluble Cd‐free NCs are sufficient to produce contrast for both fluorescence and magnetic resonance imaging techniques.